2021
DOI: 10.3390/v13102020
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and Genetic Characterization of Novel Paramyxoviruses Related to the Genus Henipavirus in Crocidura Species in the Republic of Korea

Abstract: Paramyxoviruses, negative-sense single-stranded RNA viruses, pose a critical threat to human public health. Currently, 78 species, 17 genera, and 4 subfamilies of paramyxoviruses are harbored by multiple natural reservoirs, including rodents, bats, birds, reptiles, and fish. Henipaviruses are critical zoonotic pathogens that cause severe acute respiratory distress and neurological diseases in humans. Using reverse transcription-polymerase chain reaction, 115 Crocidura species individuals were examined for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 72 publications
0
56
0
Order By: Relevance
“…Another possibility is that PBV is a marsupial-borne henipavirus. Recently, it was demonstrated the existence of rodent-borne henipavirus [10,14], from China, and shrewborne henipaviruses, from China, South Korea, Belgium, and Guinea [14][15][16][17], which further indicates the possibility of other mammals harboring henipaviruses. Although this matter remains unclear, due to lack of data about PBV genomic organization and ecological features, the marsupial-borne origin hypothesis is still supported by the high divergence of the nucleotide sequence and the isolated position of PBV in a sister clade to the bat-borne and rodent/shrew-borne subclades in the phylogenetic reconstruction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another possibility is that PBV is a marsupial-borne henipavirus. Recently, it was demonstrated the existence of rodent-borne henipavirus [10,14], from China, and shrewborne henipaviruses, from China, South Korea, Belgium, and Guinea [14][15][16][17], which further indicates the possibility of other mammals harboring henipaviruses. Although this matter remains unclear, due to lack of data about PBV genomic organization and ecological features, the marsupial-borne origin hypothesis is still supported by the high divergence of the nucleotide sequence and the isolated position of PBV in a sister clade to the bat-borne and rodent/shrew-borne subclades in the phylogenetic reconstruction.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, novel henipaviruses were described or had sequences submitted on GenBank database referring to being found in shrews, mostly of the genus Crocidura from China, South Korea, Belgium, and Guinea [14,15,16]. Besides, a presumably shrew-borne novel henipavirus, phylogenetically related to MojV, referred as Langya henipavirus, was associated to a febrile illness in patients from China, mostly farmer workers.…”
Section: Introductionmentioning
confidence: 99%
“…There is growing evidence indicating that henipaviruses, despite having mainly been detected in the Pteropus genus, may infect other genera of pteropodid bats and even microbats including P. lylei , P. hypomelanus , P. vampyrus , P. rufus , P. poliocephalus , P. scapulatus , P. conspicillatus , Eidolon dupreanum , Eidolon helvum , Rousettus madagascariensis , Carollia perspicillata, and in the insectivorous Hipposideros larvatus and Pteronotus parnellii [ 9 , 42 , 43 ]. In addition to bats, several reports have suggested that some rodent species may also harbor henipa-like viruses [ 44 , 45 ].…”
Section: Generalitiesmentioning
confidence: 99%
“…Novel HNVs continue to emerge from wildlife hosts and represent ongoing threats to human health. Initially, the Henipavirus genus comprised only HeV and NiV; however, the past two decades have witnessed the discovery of five new HNVs: bat-borne Cedar virus (CedV) and Ghanaian bat virus (GhV), rodent-borne Mojiang virus (MojV), and shrew-borne Gamak (GAKV) and Daeryong viruses (DARV) (8)(9)(10)(11). Of these novel HNVs, at least two show evidence of zoonotic potential: serological data suggests prior human exposure to GhV in West Africa (12), while MojV was first identified following a human outbreak of severe pneumonia in Chinese mine workers, all of whom died after infection (9).…”
Section: Introductionmentioning
confidence: 99%
“…Of these novel HNVs, at least two show evidence of zoonotic potential: serological data suggests prior human exposure to GhV in West Africa (12), while MojV was first identified following a human outbreak of severe pneumonia in Chinese mine workers, all of whom died after infection (9). In addition to their high potential for pathogenicity, HNVs possess a broad host range that spans at least seven mammalian orders, including bats (10,13). Cross-species viral spillover necessitates effective inter-species transmission, which first requires a virus to successfully enter the cells of diverse host species.…”
Section: Introductionmentioning
confidence: 99%